Cytoreductive nephroureterectomy for treatment of upper urinary tract urothelial carcinoma initially diagnosed as node-positive - Shu-Yu Wu; Chi-Ping Huang; Chao-Hsiang Chang; Steven K. Huang; Wen-Hsin Tseng; Wei-Ming Li; Hung-Lung Ke; I-Hsuan Alan Chen; Jen-Tai Lin; Jen-Shu Tseng; Wun-Rong Lin; Yuan-Hong Jiang; et al. (Scientific Reports)
Abstract Urothelial carcinomas of the upper urinary tract (UTUC) are rare tumors with a high malignancy degree. Radical nephroureterectomy (RNU) with bladder cuff excision remains one of the standard treatments in clinically localized or locally advanced UTUCs. However, the role of cytoreductive RNU in treating clinically lymph node-positive (N+) UTUCs remains unclear. A nationwide retrospective study was conducted by the Taiwan UTUC Collaboration Group from July 1988 to June 2022. Patients with clinical N + UTUC before initiation of cancer therapy were included in this study. Initial clinically node-positive disease was noted in 288 (5.4%) of the 5,301 patients. Of the patients, 239 (83%) patients underwent RNU. UTUC-related mortality was markedly higher among patients not receiving RNU than among those who underwent surgery (69.4% vs. 36%). After adjusting for the effects of stepwise enrolled parameters, multivariate analysis showed that undergoing RNU (or not) and smoking (or not) were the only independent predictors of overall survival (OS). After adjusting for the effects of significant stepwise enrolled variables, multivariate analysis showed that RNU and smoking (or not) were the only independent predictors of cancer-specific survival (CSS). Our findings showed that RNU is associated with better OS and CSS in Taiwanese patients with N + UTUC. Common patient characteristics and most cancer characteristics were not related to the outcome. Our results provide new evidence on the efficacy of RNU for patients with N + UTUC, which could alter and guide the direction of future treatment guidelines.